Using goal directed task analysis to identify situation awareness requirements of advanced paramedics - Abd Hamid, Harris Shah; Waterson, Patrick (2010)
Advanced paramedics, known in the UK as emergency care practitioners (ECPs) are employed by ambulance services to meet the demand for urgent care in the community. The role has been evaluated in terms of patient outcomes. To further understand and evaluate the role, Goal Directed Task Analysis (GDTA) was conducted. Based on the analysis, situation awareness requirements among ECPs were identified. The results of the GDTA are presented and their implication discussed in terms of goal hierarchy structure, patient as source of information, and sociotechnical system. We discuss recommendations for the role with regard to the ECPs' SA. Further SA studies to evaluate and develop the ECP role are also outlined.